Information System For Recording Teacher Activities And Student Achievements At Smk Negeri 1 Suak Tapeh - Rangga Sutrisna; Ahmad Sanmorino; Agustina Heryati (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
This study aims to develop a web-based information system for recording teacher activities and student achievements at SMK Negeri 1 Suak Tapeh. The background of this research lies in the school’s previous manual data management method using Microsoft Word and Excel, which often caused inefficiency and data loss. The objective is to create a structured and accessible system that improves the accuracy, transparency, and accountability of institutional data management. The system was developed using the Agile Scrum methodology to ensure iterative development and continuous user involvement. PHP was used as the main programming language, MySQL as the database, and Tailwind CSS for responsive interface design. The system integrates five user roles Operator, Teacher, Head of Administration, Principal, and Vice Principal each with specific access privileges according to their institutional responsibilities. Black-box testing was applied to evaluate system functionality, focusing on the accuracy of input and output processes. The results show that all system modules, including activity submission, approval workflow, achievement management, and report generation, functioned as expected and met user requirements. The system successfully replaced the manual process with a digital platform that enhances efficiency and transparency. Furthermore, it provides real-time access through responsive web design across desktop and mobile devices. Future improvements may include integrating data analytics, notification systems, and enhanced security layers to support the school’s digital transformation.